2018
DOI: 10.4025/actascibiolsci.v40i1.39073
|View full text |Cite
|
Sign up to set email alerts
|

<b>Germination and growth of <i>Albizia niopoides</i> (Bentham) Burkart (Fabaceae)

Abstract: Albizia niopoides (Bentham) Burkart, known as farinha seca, is an arboreal, deciduous and pioneer plant that can be found in the semi-deciduous forest in the Paraná basin. The study on the germination and growth of the plant is fundamental for better knowledge about the establishment and regeneration of the species. Aiming to verify the germination of A. niopoides and subsequent growth, green seeds and brown seeds were germinated in a germination chamber and growth parameters were evaluated at 60, 90, and 180 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
0
0
1
Order By: Relevance
“…Os frutos classificados como dos estádios 3 e 4 apresentaram maior porcentagem de emergência (E) e maior índice de velocidade de emergência (IVE) que os demais, seguidos do estádio 2, pelo estádio 1 com os menores valores. Barbeiro et al (2018), em estudo com germinação e crescimento de Albizia niopoides (Benth.) Burkart, com sementes de cores verde e marrom, verificaram que as sementes marrons foram mais vigorosas que as verdes, apresentando maior porcentagem de emergência, IVE e IVG, e concluíram que as sementes marrons geraram mudas com qualidade superior.…”
Section: Resultsunclassified
“…Os frutos classificados como dos estádios 3 e 4 apresentaram maior porcentagem de emergência (E) e maior índice de velocidade de emergência (IVE) que os demais, seguidos do estádio 2, pelo estádio 1 com os menores valores. Barbeiro et al (2018), em estudo com germinação e crescimento de Albizia niopoides (Benth.) Burkart, com sementes de cores verde e marrom, verificaram que as sementes marrons foram mais vigorosas que as verdes, apresentando maior porcentagem de emergência, IVE e IVG, e concluíram que as sementes marrons geraram mudas com qualidade superior.…”
Section: Resultsunclassified
“…According to Oliveira et al (2019), the four species studied had a minimum of three pairs of leaves, a criterion adopted by forestry companies to classify seedling quality. superior results were obtained by Barbeiro et al (2018), in which 'Farinha Seca' had 12.3 leaves. This information, despite the differences in treatments, management practices and the region where they were developed, indicate that topsoil may become an option for seedling production, in view of the importance of the number of leaves.…”
Section: Number Of Leavesmentioning
confidence: 87%
“…= 36.6 cm), however, without significant effect for 'Ipê Branco' (p > 0.05). In general, although the species 'Canafístula', 'Farinha Seca' and 'Ipê Branco' had averages below 20 cm, it is possible that the evaluation period (90 DAP) was insufficient, considering that Portela et al (2001), at 150 DAP, Barbeiro et al (2018) and Cardorin et al (2021), at 180 DAP, observed mean heights of 20.4, 38.2 and 28.9 cm for the three species, respectively.…”
Section: Seedling Heightmentioning
confidence: 99%